Delivering Universal and Sustainable Water Services : Partnering with the Private Sector - Menzies, Iain (World Bank, Washington, DC, 2016)
A dedicated goal for water has recently been endorsed by the United Nations General Assembly as part of the sustainable development goal (SDG) framework. This study provides an assessment of the global costs of meeting the WASH-related targets of Goal #6. The targets assessed include achieving universal and equitable access to safe and affordable drinking water for all (target 6.1), achieving access to adequate and equitable sanitation and hygiene for all, and ending open defecation (target 6.2). The estimates include 140 countries, or 85% of the world's population, focusing on developing countries. Costs estimated cover those of capital investment, program delivery, operations, and major capital maintenance. Three main findings are as follows: 1. Extending basic WASH services to the unserved costs US$ 28.5 billion per year from 2015 to 2030, or 0.10% of global product. This financing requirement is equivalent, in orders of magnitude, to the 0.12% global capital spending to serve the unserved with improved water supply and sanitation during the MDG period. However, in some regions significantly more than 0.10% additional GDP needs to be spent on basic WASH services to achieve universal access. 2. The capital investments required to achieve targets 6.1 and 6.2 amounts to $ 112 billion annually or about three times current investment levels (0.38% of global product). 3. Sustained universal coverage requires more than capital inflows: financial and institutional strengthening will be needed to ensure capital investments translate into effective service delivery. It is critical to consider the ongoing finances required to ensure the proper operations of these services. Due to the many uncertainties in underlying data and also methodological choices, the cost estimates reported in this study should be used with caution. For national policy making and resource allocation, countries are encouraged to conduct their own costing studies or investment plans